A METHOD FOR DETERMINATION OF SEPARATION PROPERTIES OF MEMBRANES - Grujić, A.; Stijepović, M.; Stajić Trošić, J.; Ilić, J.; Nedeljković, D. (Journal of Engineering & Processing Management, 2015)
In this study, design of lab scale device for determination of separation properties of membranes is presented and analyzed. Device operates with different gas pressure between chambers, whereby gas streams perpendicular to the membrane. Using appropriate acquisition system and applying mathematical formulas, mechanism for gas transfer through the membrane is determinate. Polymer membranes based on zeolite are synthesized and tested by lab scale device. The membranes with various content of zeolite are tested with CO 2 gas until optimal composition of membrane components is established. Beside good mechanical and structural properties of applied membrane, suitable values of permeability with good agreement with the literature data are obtained.